Review on the Relationship of Absorptive Capacity with Interorganizational Networks and the Internationalization Process - L. F. Agramunt; J. M. Berbel-Pineda; M. M. Capobianco-Uriarte; M. P. Casado-Belmonte (Complexity)
There is evidence about the international competitiveness of Small and Medium Enterprises having a close relationship with their absorptive capacity and internationalization networking, and for that reason, it is relevant to find out the main trends in this field of knowledge. The objective of this study is to provide a bibliometric analysis of the status of the existing research in the field to recognize main topics and help identify research gaps. This study was done through a review of 1,710 documents published about this relationship from the Scopus and Web of Science databases (1994–2018), using as processing software application that employs two combinations of terms associated with Boolean operators. This was taken into account in order to optimize the accuracy of the search and to facilitate large data capture. The results show that these studies are in a period of high production and concentrated in a few countries and researchers’ networks in the United States, the People’s Republic of China, and some European countries. Moreover, the trend words used by researchers are those which link absorptive capacity with networking, open innovation, and firm performance.